2017
DOI: 10.1111/jocn.13952
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and its association with resilience in nurses: A cross‐sectional study

Abstract: Aims and objectives: To investigate the prevalence and extent of burnout on nurses and its association with personal resilience.Background: With the worldwide shortage of nurses, nurse burnout is considered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
204
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(242 citation statements)
references
References 51 publications
(65 reference statements)
31
204
1
6
Order By: Relevance
“…Conversely, since recent studies have demonstrated that second‐hand tobacco smoke exposure is associated with addictive behaviours and psychological distress (Okoli ; Zeng & Li ), greater second‐hand tobacco smoke exposure may increase a person's vulnerability to STS, but this association is merely speculative at this point. In addition, having a history of a behavioural health problem and recent alcohol use were variables also associated with BO, as has been found in other studies (Creedy et al ; Guo et al ; Rath et al ). However, sleep quality was the single behavioural variable associated with CS, BO, and STS.…”
Section: Discussionsupporting
confidence: 80%
“…Conversely, since recent studies have demonstrated that second‐hand tobacco smoke exposure is associated with addictive behaviours and psychological distress (Okoli ; Zeng & Li ), greater second‐hand tobacco smoke exposure may increase a person's vulnerability to STS, but this association is merely speculative at this point. In addition, having a history of a behavioural health problem and recent alcohol use were variables also associated with BO, as has been found in other studies (Creedy et al ; Guo et al ; Rath et al ). However, sleep quality was the single behavioural variable associated with CS, BO, and STS.…”
Section: Discussionsupporting
confidence: 80%
“…The same results have been found in several other studies as well (Amiri et al, ; Li et al, ). However, few studies found higher levels of emotional exhaustion among male nurses (Lin, Jiang, & Lam, ) and some studies did not find a significant relation between exhaustion and gender (Guo et al, ; Schadenhofer, Kundi, Abrahamian, Stummer, & Kautzky‐Willer, ). It is possible that male nurses can better manage emotional situations and are less affected by emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Before the COVID-19 pandemic there was already concern about nurses' mental health and well-being in relation to depression, anxiety, anger, irritability and burnout (Tahghighi et al 2017, Guo et al 2018. Critical care nurses, for example, are at risk of burnout if they have reduced resilience (Jackson et al 2018) and are at a high risk of developing PTSD (Mealer et al 2012), which is a particular concern for nurse leaders during the COVID-19 pandemic.…”
Section: Resilience In Healthcare Workersmentioning
confidence: 99%